2008
DOI: 10.1002/pmic.200700763
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium lipid rafts contain proteins implicated in vesicular trafficking and signalling as well as members of the PIR superfamily, potentially implicated in host immune system interactions

Abstract: Plasmodium parasites, the causal agents of malaria, dramatically modify the infected erythrocyte by exporting parasite proteins into one or multiple erythrocyte compartments, the cytoplasm and the plasma membrane or beyond. Despite advances in defining signals and specific cellular compartments implicated in protein trafficking in Plasmodium-infected erythrocytes, the contribution of lipid-mediated sorting to this cellular process has been poorly investigated. In this study, we examined the proteome of cholest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
39
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 65 publications
3
39
0
Order By: Relevance
“…Non-infected red blood cells were lysed and included as controls in every analysis to discard noise due to the detection of sugar nucleotides carried away from the erythrocytes. The suspension was incubated on ice until lysis was completed (ϳ10 min) (29). Pellets were washed three times with cold phosphate-buffered saline (PBS), and sugar nucleotide analysis was performed as described elsewhere (30).…”
Section: Methodsmentioning
confidence: 99%
“…Non-infected red blood cells were lysed and included as controls in every analysis to discard noise due to the detection of sugar nucleotides carried away from the erythrocytes. The suspension was incubated on ice until lysis was completed (ϳ10 min) (29). Pellets were washed three times with cold phosphate-buffered saline (PBS), and sugar nucleotide analysis was performed as described elsewhere (30).…”
Section: Methodsmentioning
confidence: 99%
“…Detected proteins only partially overlap with DRM components of the P. falciparum late schizonts (16,17) or the mixed blood stages of the rodent malaria agent P. berghei (18). Immunolocalization of selected DRM-associated proteins indicated that these assemblies may reside in both exported compartments (PVM, MCs) and intracellular membranes/organelles.…”
mentioning
confidence: 99%
“…A number of studies have identified Plasmodium proteins that contain signature sequence motifs, the host cell targeting signal or the Plasmodium export element (PEXEL), that target these proteins into the infected erythrocytes (10,11). Recent proteomics analyses have identified novel proteins in the raftlike membranes of the parasite and on the surface of infected erythrocytes (12,13). P. falciparum translationally controlled tumor protein (PfTCTP), a homolog of the mammalian histamine-releasing factor, has been shown to be released into the culture supernatant from intact as well as ruptured infected RBCs and causes histamine release from human basophils and IL-8 secretion from eosinophils (14).…”
mentioning
confidence: 99%